KEMAMPUAN MENENTUKAN IDE POKOK PARAGRAF MELALUI MODEL COOPERATIVE SCRIPT DI KELAS V SDN 1 BULANGO SELATAN KABUPATEN BONE BOLANGO - WAYAN RUSMINI, NI; HUSAIN, RUSMIN; HALIDU, SALMA; TRIYANTY PULUKADANG, WIWY; KATILI, SUKRI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This research aims to improve students' ability to determine main ideas of paragraphs through the Cooperative Script model. This research adopts a Classroom Action Research approach, utilizing test, observation, and documentation methods for data collection. The subjects of this research are 24 students of Grade V. The initial observation reveals that out of 24 students, 4 students (17%) are categorized as capable, while 20 students (83%) are categorized as incapable. After implementing classroom actions, an improvement is observed in students' ability to determine the main ideas of paragraphs. In Meeting I of Cycle 1, 8 students (33%) are categorized as capable, while 16 students (67%) are categorized as incapable. In Meeting II of Cycle I, the number of capable students increases to 14 (58%), while 10 (42%) remain incapable. Finally, in Cycle II, the final results show that 21 students (87%) are categorized as capable, while only 3 students (13%) are still categorized as incapable. Thus, based on these results, it can be concluded that the Cooperative Script model effectively improves students' ability to determine paragraph main ideas in Grade V at SDN 1 Bulango Selatan, Bone Bolango Regency. ABSTRAK Tujuan penelitian ini adalah untuk meningkatkan kemampuan siswa dalam menentukan Ide Pokok Paragraf melalui model Cooperative Script di Kelas V SDN 1 Bulango Selatan Kabupaten Bone Bolango. Penelitian ini menggunakan pendekatan tindakan kelas. Teknik pengumpulan data yang digunakan adalah tes, observasi dan dokomentasi. Subjek dalam penelitian ini adalah siswa kelas V yang berjumlah 24 orang. Hasil penelitian pada Siklus I Pertemuan I siswa dengan kategori mampu berkisar 33% dan kategori tidak mampu berkisar 67%. Selanjutnya pada Siklus I Pertemuan II siswa dengan kategori mampu berhasil meningkat berkisar 58% dan kategori tidak mampu berkisar 42%. Kemudian pada Siklus II siswa mengalami peningkatan yang signifikan dengan kategori mampu 87% dan kategori tidak mampu 13%. Hal ini, menunjukkan bahwa penelitian ini telah mencapai indikator keberhasilan tindakan. Dengan demikian, dapat disimpulkan bahwa melalui model Cooperative Script dapat meningkatkan kemampuan siswa dalam menentukan ide pokok paragraf di kelas V SDN 1 Bulango Selatan Kabupaten Bone Bolango.